Tax compliance costs: a business administration perspective - Sebastian Eichfelder; Michael Schorn (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2009)
The paper analyses the relationship of tax compliance costs and business strategy. Due to instruments, like information technology, simplified cash accounting or outsourcing compliance activities to tax advisers, private businesses have a set of strategies to optimize their tax compliance cost burden. Under the assumption of rational choice a private business should choose a cost-optimal administration strategy. In spite of that we find empirical evidence for small German businesses using only insufficiently the support of external tax advisers. Therefore, a considerable number of small businesses in Germany could reduce their compliance cost burden by a higher degree of outsourcing tax processes. In contrast, we find no significant evidence for a cost reduction by an electronic data interchange with the tax and social insurance authorities or by a simplified cash accounting method for tax purposes.
Keywords: H25; H26; L23; L24; 330; Tax complexity; tax compliance costs; bureaucracy costs; tax administration; administration strategy; business strategy; outsourcing; contracting out; e-filing; electronic data interchange; cash accounting